2023
DOI: 10.3390/su15021057
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Young Adult Consumers’ Environmentally and Socially Responsible Apparel Consumption

Abstract: Social and environmental responsibility of apparel sector has been drawing rising attention of policymakers and researchers in recent years. One possible solution to curb the detrimental effects caused by the clothing industry is to invoke more responsible demand of its heavy users, such as young clothing customers. This study aims to examine a model of the determinants of environmentally and socially responsible clothing consumption of young adult customers in a developing economy. The study has been performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…However, previous studies highlighted that the likelihood of visiting companies with green initiatives and the general consumer green behavior depends on gender and levels of income [121][122][123]. Similarly, a study conducted on factors that influence consumers to purchase in companies with green initiatives found that gender has a significant relationship with companies participants are likely to purchase in, with women purchasing in companies with green initiatives more than men [124]. These results have contributed to the literature pertaining to green consumerism.…”
Section: Companies' Green Initiativesmentioning
confidence: 78%
“…However, previous studies highlighted that the likelihood of visiting companies with green initiatives and the general consumer green behavior depends on gender and levels of income [121][122][123]. Similarly, a study conducted on factors that influence consumers to purchase in companies with green initiatives found that gender has a significant relationship with companies participants are likely to purchase in, with women purchasing in companies with green initiatives more than men [124]. These results have contributed to the literature pertaining to green consumerism.…”
Section: Companies' Green Initiativesmentioning
confidence: 78%
“…However, this method can only demonstrate whether the research factors have a significant impact on green consumption, but cannot determine the degree of influence of the factors. That is to say, this method cannot provide detailed information on the importance of various factors in SEM, nor can it identify which are the critical influencing paths in the influencing factor index [53,54]. Therefore, having constructed the influencing factor system, we used the Delphi method to screen and optimize the initial set of influencing factors, and formed the final influencing factor system of residents' GCB.…”
Section: Methodologiesmentioning
confidence: 99%
“…The current research complements Jain et al's (2022) study in India because Spain's tourists have quite different characteristics. Other prior investigations have been limited by their cross-sectional nature (Vlastelica et al, 2023), as well as samples made up of participants from a single country, so longitudinal studies are needed to fill this gap. The present research provides a starting point for future longitudinal studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Responsible consumption is an integral part of the United Nations' sustainable development (SD) goals as it contributes to the achievement of long-term SD (Jain et al, 2022;Patwary, 2023). Consumers who incorporate social and environmental values into their buying decisions engage in responsible consumption regardless of the sector in which their purchases take place (Do Paço et al, 2019;Vlastelica et al, 2023). Individuals' values reflect their personal objectives and influence how their beliefs are expressed through responsible behavior (Yuriev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation